ANALYSIS OF THE EFFECT OF INTEGRATING DIGITAL GAME-BASED DECISION-MAKING INTO THE APPROPRIATE TEACHING OF BUSINESS ETHICS - Chen, Che-Fei (Graduate Program of Universitas Tarumanagara, 2023)
As the increasing emphasis of game-based learning on teaching strategies, many researchers in dictated that implanting game-based learning strategies, which include the enjoyment and tasks for student to pass, in the digital learning system can guide students to enhance their learning motive to win game. Many teaching strategies were developed to improve programming skills instead of traditional business ethical class lecture. Among them, game-based learning are applied to enhance students learning. Nonetheless, they fail to engage students in deep thinking and reflections. To cope with this issue, a two-tier test-based learning system is proposed to enhance students’ learning performances and the flow experience in business ethical courses in this study.